Switching of biologic disease modifying anti-rheumatic drugs in patients with rheumatoid arthritis in a real world setting. (April 2014) - Meissner, Brian; Trivedi, Digisha; You, Min; Rosenblatt, Lisa
Abstract Objectives: This study examined total healthcare costs and rates of patients with rheumatoid arthritis (RA) who switch biologic disease-modifying anti-rheumatic drug (bDMARD) therapy in a real world setting. Methods: A retrospective longitudinal analysis was conducted in patients with RA using IMS PharMetrics Plus database from 1/1/2004 to 3/31/2010. The first-line cohort included patients newly initiated on abatacept or the tumor necrosis factor-alpha inhibitors (anti-TNFs) adalimumab, etanercept, or infliximab, with 12 months of continuous follow-up. The second-line cohort included patients initiating a bDMARD with evidence of a different bDMARD within the previous 2 years and with 12 months of continuous follow-up. Switching was defined as a different bDMARD claim within a 200% gap in days supply from the previous bDMARD claim. Non-switchers stayed on their bDMARD in the follow-up period. Monthly total healthcare costs for switchers and non-switchers and rates of bDMARD switching were examined. Switch rates for each bDMARD were also compared. Results: First-line switchers had significantly higher monthly total healthcare costs after the switch than non-switchers (3759 vs 2343; p < 0.05), as did second-line switchers (3956 vs 2616; p < 0.05). First-line abatacept (2.1%) had significantly lower rates of switching compared to adalimumab (9.5%), etanercept (9.0%), and infliximab (5.5%). Second-line abatacept (8.0%) had significantly lower rates of switching compared to adalimumab (16.7%), etanercept (14.4%), and infliximab (14.3%). Limitations: There are no clinical data available in this database and, therefore, this study did not examine the clinical drivers of healthcare costs and switch rates. Conclusions: Monthly total healthcare costs were higher for bDMARD switchers following the switch compared to non-switchers. Patients on abatacept switched less frequently than patients on anti-TNFs. This study highlights the need to identify patients who are likely to switch in order to ensure they receive the appropriate therapy which may improve outcomes and decrease healthcare costs.